245 Risk factors for occupational drowning in Lake Victoria's small-scale fisheries. (20th November 2022) - Roland, Rachel; Mugema, Arthur; Lukanga, Editrudith; Mecrow, Tom; Sindall, Becky
Abstract : Background: Previous studies have identified high drowning rates amongst fishers on Lake Victoria, but little is known about the root causes of these occupational deaths. This presentation will summarise findings from a qualitative research study conducted in Tanzania, including risk factors at individual, community, industry, and policy levels. Methods: Seven sites were selected to represent the range of fishing communities around the Lake (island vs mainland, peri-urban vs rural, primary catch). Focus group discussions to understand drowning risk and impacts were held with stakeholders along the fishing value chain including fishers, boat owners and builders, and fish traders/processors. Key informant interviews were conducted with local government authorities to understand fishing and village governance in relation to drowning. Results: Common risk factors included community-wide lack of water safety awareness, fishers' lack of safe boating skills including navigation and use of weather reports, poor maintenance of boats, and use of alcohol as a 'boost' during overnight fishing trips. In most locations, safety equipment was unaffordable and inaccessible. Fishing regulations were poorly enforced, though one community acted as a positive deviant with a well-coordinated Beach Management Unit (BMU) providing enforcement and regular support to fishers, fish workers and the surrounding community. Conclusion: Small-scale fishing on Lake Victoria is a high-risk profession but a multi-strategy approach could foster safer working practices. Learning Outcomes: Drowning prevention interventions on Lake Victoria must include capacity-strengthening for BMUs and village leadership to enact existing regulations, as well as providing safe boating training to fishers.